Stem cell mobilizating effect of heparin in patients undergoing autologous stem cell transplantation - Merter, Mustafa; Sahin, Ugur; Ilhan, Osman; Beksac, Meral (Wiley, 2023)
Background: Adequate stem cell collection is essential for successful stem cell transplantation. Heparin enhances stem cell mobilization by competing with heparin sulfate proteoglycans. Heparin is also used as an anticoagulant before leukapheresis. Here, we evaluated the effects of heparin on stem cell mobilization in patients who underwent autologous stem cell transplantation (ASCT).Methods: We evaluated patients who underwent ASCT. Patients were divided into two groups: those who received heparin plus citrate (heparinized patients) and those who received citrate only (nonheparinized patients) for anticoagulation. Univariate and multivariate analyses were also performed. The collection efficiency 2 (CE2) for CD34+ cells was calculated and compared between heparinized and nonheparinized patients.Results: This study included 1017 patients. There were 478 (47%) heparinized and 539 (53%) nonheparinized patients. The number of collected CD34+ cells was significantly higher in heparinized patients (P < .00001). The multivariate analyses showed that using heparin was an independent positive factor for collected CD34+ cells (adj-R-2 = 0.744; F = 369.331, P < .00001). CE2 was significantly higher in heparinized patients than in nonheparinized patients (66.8% vs 52.1%; P < .00001). The rate of collecting at least 2 x 10(6)/kg CD34+ cells was 3.3 times higher for heparinized patients in poor mobilizers (P < .00001). Heparinized patients had significantly higher total nucleated and mononuclear cell counts (P < .00001 and <.00001, respectively).Conclusion: Heparin enhances stem cell collection and increases CE2. The use of heparin may reduce the need for other strategies to increase stem cell mobilization.
Keywords: CE2; heparin; MNC; stem cell mobilization; TNC